ANALISIS SISTEM PENGELOLAAN PENGADUAN MASYARAKAT PADA PUSAT PENGELOLAAN PENGADUAN MASYARAKAT (P3M) KOTA SEMARANG - Ayuningtyas Dyah Pitaloka Subagyo; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
As a form of response to the need for complaint management in the City of Semarang through Semarang Mayor Regulation Number 34 of 2017, a community complaint unit was formed which became known as the